The Impact of Hyperglycemic Emergencies on the Kidney and Liver. (24th October 2013) - Bai, Feng; Jiang, Fang-fang; Lu, Jun-jie; Ma, Shao-gang; Peng, Yi-gen; Jin, Yue; Xu, Wei; Cheng, Jian-ping; Wu, Hai-feng
Abstract : Studies on the alterations of liver and kidney function parameters in patients with diabetic ketoacidosis (DKA) and diabetic ketosis (DK) were limited. Participants with DKA, DK, non-DK, and healthy controls were enrolled in the current study. Parameters of liver and kidney function were measured and evaluated. The patients with DKA had higher levels of plasma glucose, hemoglobin A1c (HbA1c), uric acid, and creatinine but lower levels of transferases and protein compared with the other three groups (P < 0.05 for all). The patients with DK had higher levels of plasma glucose and HbA1c but lower levels of glutamyl transpeptidase and protein compared with the non-DK and control groups (P < 0.05 ). Prealbumin levels were significantly reduced in the severe DKA patients compared with the mild/moderate DKA patients. Serum prealbumin levels were correlated with albumin levels (r = 0.401, P = 0.010 ), HCO3 (r = 0.350, P = 0.027 ), and arterial pH (r = 0.597, P < 0.001 ) in the DKA patients. A diagnostic analysis showed that lower prealbumin levels significantly reflected the presence of hyperglycemic emergencies (P < 0.001 ). Liver and kidney function parameters deteriorated, especially in DKA. Prealbumin levels can be of value in detecting the presence of hyperglycemic crisis. This clinical trial is registered with ChiCTR-OCH-12003077 .